Legal regulation in the tourism industry in Ukraine - Melnykovych M. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
The purpose of this work is to analyze the importance of ensuring proper legal regulation of legal relations in the field of tourism. The emphasis is made on the fact that legal relations in the field of tourism are complex, and therefore legal regulation should be comprehensive and consistent with the realities of today. At the international level, the understanding of “tourism” is multifunctional and is considered, on the one hand, as an activity of people’s movement and a means for economic development of the territory, and on the other hand. Given that the Ukrainian state declares tourism one of the priority areas of economic and cultural development and has undertaken to create the necessary conditions for the development of tourism activities, the issue of normative and legal support for the regulation of tourism relations is one of the priority, if not the first priority. Methodology: The methodology includes a comprehensive analysis of the problem, generalization of the state of the current legal material on the issue raised and the formation of relevant conclusions and recommendations. The following methods of scientific knowledge were used in the course of the study: terminological, systemic-structural, comparative-legal and analysis method. Results: The results of the study revealed the importance of ensuring proper legal regulation of public relations in the field of tourism, in particular, the need for a detailed analysis of legal relations in this complex industry and the creation of a sustainable and effective legislative framework for its development was substantiated. Special attention is paid to the importance of involving the public in the work on tourism development (including in the direction of legislative content) and the emphasis is placed on the advisability of identifying tourism law as a separate branch of law. The analysis of individual normative legal acts showed that the legal regulation of the tourism industry in Ukraine has deep roots, which, in turn, can serve as a basis for work in the direction of strengthening the legal regulation of tourism relations. Scientific novelty: During the research, the complexity of the situation regarding the state of legal regulation of legal relations in the field of tourism was emphasized. It was proposed to approach the solution of the problem from the point of view of considering the possibility of creating tourism law as a separate branch of law. Practical significance: The results of the study can be used in lawmaking activities in the implementation of state legal policy in the field of tourism development, as well as for further theoretical research in this direction.